Neutron radiography and current distribution measurements for studying cathode flow field properties of direct methanol fuel cells. (15th August 2013) - Schröder, A.; Wippermann, K.; Arlt, T.; Sanders, T.; Baumhöfer, T.; Kardjilov, N.; Hilger, A.; Mergel, J.; Lehnert, W.; Stolten, D.; Banhart, J.; Manke, I.
SUMMARY The influence of the cathode flow field properties on the water distribution and performance of direct methanol fuel cells (DMFCs) was studied. All measurements were performed with DMFC stack cells (A = 314.75 cm2). The local and temporal water distributions in the flow field channels during DMFC operation were visualized by means of through‐plane neutron radiography. Current and temperature distributions were measured simultaneously by the segmented cell technology. Additionally, the time‐dependent current distribution, cell performance and pressure drop were measured. Cathode flow field designs with channel and grid structures were compared. The cathode flow field channels were impregnated by either hydrophobizing or hydrophilizing agents or used as received. It turned out that hydrophobized and partially also untreated flow fields cause large water droplets in the cathode channels. The water droplets cause a blocking of the air flow and consequently a lower and more unstable (fluctuating) performance, less steady current and temperature distributions, and higher pressure drops between cathode inlet and outlet. Because of their two‐dimensional design, grid flow fields are less prone to water accumulations. The best results are achieved with a hydrophilized grid flow field that has a channel depth and width of 1.5 mm each ('C‐GR15'). Copyright © 2013 John Wiley & Sons, Ltd.